Respuesta :
[tex]\bf f(x)=\cfrac{2x^2-5x+2}{x-3}\impliedby
\begin{array}{llll}
\textit{now, we can do a quick synthetic}\\
\textit{division, since the divisor is}\\
x-3
\end{array}\\\\
-------------------------------\\\\
\begin{array}{r|rrrrl}
3&&2&-5&2\\
&&&6&3\\
--&&--&--&--\\
&&2&1&\boxed{5}&\leftarrow remainder
\end{array}\\\\
-------------------------------\\\\
\textit{so the quotient is }2x+1\impliedby \textit{oblique asymptote}\implies y=2x+1[/tex]
Answer:
The answer is y = 2x + 1
Step-by-step explanation:
Trust.